Career advancement of professional nurses at a regional hospital in Gauteng - Crescelda L. van Biljoen-Mokhotla; Agnes Makhene (AOSIS, 2023)
Background: Career advancement is of importance to professional nurses and a motivation for those who desire to occupy leadership positions. However, there were perceived barriers enunciated by participants, which were seen as contributory factors that hinder their progression in the institution. Objectives: The objective of the study was to explore and describe the perceptions of professional regarding their career advancement. Method: The study was conducted at a regional hospital in Gauteng. A qualitative, exploratory, descriptive design that is contextual was used. Non-probability purposive sampling method was used to draw the sample from a target population of professional nurses. Individual semi-structured interviews were conducted with 10 professional nurses to obtain in-depth information on their perceptions. Tesch's method of qualitative data analysis was used. Lincoln and Guba's strategies of credibility, dependability, confirmability and transferability were used to establish trustworthiness of the study. Ethical considerations were applied throughout the study. Results: A lack of recognition of postgraduate qualifications, no opportunities for self-identification of interest to lead, no mentoring processes for potential leader and succession planning and emotional experiences were barriers to career advancement. The researcher recommended that recognition of further qualifications, enhancement of self-identification for leadership roles, mentoring of young professionals for leadership and succession planning be considered to enhance career development of the professional nurses. Conclusion: The findings suggest that professional nurses encounter significant challenges to career advancement in this regional hospital. Contribution: Nurse managers to identify, mentor and support professional nurses for leadership positions in their career.